Translating corporate strategy into project strategy : realizing corporate strategy through project management - Morris, Peter; Jamieson, Ashley (Project Management Institute, 2004)
Considered the new silver bullet in guiding corporate strategy, Translating Corporate Strategy into Project Strategy, examines how project management tools and principles can be used to effectively advance business strategy. Through case studies from a variety of industries, the authors demonstrate how successful organizations move beyond mission statements and five-year plans to create the processes that are necessary to carry out time-oriented goals and projects. In addition to examining these successes, the authors also identify effective strategy implementation processes, define the relevant terms using the standards of PMIs PMBOK® Guide, outline staff roles and responsibilities, and offer several different models of personnel structure and capabilities that reflect project management principles and methods. Offering a compelling look into yet another way the project management profession is impacting business results, this book is an indispensable tool for business leaders at all levels.